MENGKAJI PERAN UN WOMEN DALAM MENGATASI KEKERASAN TERHADAP PEREMPUAN DAN MEWUJUDKAN KESETARAAN GENDER MELALUI PERSPEKTIF FEMINISME - Iqbal Ramadhan; Innesia Ma’sumah (Jurnal Asia Pacific Studies, 2018)
This research discusses about the role and effectiveness of UN Women as the real implementation of the Feminist paradigm and as an International Organization that upholds women's right in solving important issues related to women's rights, like violence against women and gender inequality. To analyse the issue on this journal, authors uses gender concept and feminist securitical approach. It also gives a stand point about the two main paradigms of International Relations, Realist and Liberalist, and its relation to Feminists regarding gender inequality and violence on women. The result of this research is that UN Women is quite effective in dealing with Feminist issues although it has not experienced significant improvement. However, UN Women's efforts should be appreciated for fighting for women's rights. Keywords: UN Women, Feminist, Violence against Women, Gender Inequality